Meningkatkan Hasil Belajar Matematika Dengan Menerapkan Model Pembelajaran Student Team Achievement Division - Sinaga, Mesi (JURNAL GLOBAL EDUKASI, 2019)
Abstract: This study aims to improve mathematics learning outcomes material simplify and sort fractions with learning models Student Team Achievement Division students grade VI SDN 014732 Huta Bagasan district Bandar Pasir Mandoge academic year 2018/2019. This class action research was carried out in 2 cycles. The subject of this study was grade VI students of SDN 014732 Huta Bagasan totaling 29 students, data were collected through observation, interviews, tests, and study documentation. The research results obtained learning outcomes in the first cycle to achieve classical learning completeness by 70% after and cycle II there was an increase in classical learning completeness to reach 85% means there was an increase of 15%. Keywords: student team achievement division, fractions Abstrak: Penelitian ini bertujuan untuk meningkatkan hasil belajar Matematika materi menyederhanakan dan mengurutkan Pecahan dengan model pembelajaran Student Team Achievement Division siswa kelas VI SDN 014732 Huta Bagasan kec. Bandar Pasir Mandoge TP. 2018/2019. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus. Subjek penelitian ini siswa kelas VI SDN 014732 Huta Bagasan yang berjumlah 29 orang siswa, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Hasil penelitian diperoleh hasil belajar pada siklus I mencapai ketuntasan belajar klasikal sebesar 70% setelah dan siklus II terjadi peningkatan ketuntasan belajar klasikal hingga mencapai 85% berarti terdapat peningkatan sebesar 15 %. Kata kunci: student team achievement division, pecahan